PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEADS TOGETHER UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SEKOLAH DASAR - Mariah Ulfah (Universitas Pendidikan Indonesia, 2020)
This research aims to: (1) describe the implementation of learning mathematics with application of cooperative learning model of NHT type in improving problem-solving abilities of fifth grade students at SDN Perumnas 02; and (2) describe the mathematical problem solving abilities increase abilities of fifth grade students at SDN Perumnas 02 with the implementation of cooperative learning model of NHT type in learning Mathematics. The method used is classroom action research Kemmis and Mc. Taggart models conducted in two cycles with qualitative and quantitative research approaches. Results from this study are: (1) the implementation of learning mathematics with application of cooperative learning model of NHT type of cycle I to cycle II of fifth grade students at SDN Perumnas 02, the better. Headband as numbering media to motivate students to learn. Giving the problem at this stage of questioning which is designed in the form of worksheets and given to each student develop a sense of personal responsibility so that when heads together students discuss with the group in solving problems. External motivation given teacher support internal motivation is able to create and enable the whole group to discuss; and (2) Application of cooperative learning model of NHT type can improve mathematical problem-solving abilities.